A comprehensive approach to adolescent suicide prevention: insights from a narrative review perspective - Baldini, Valentina; Gnazzo, Martina; Varallo, Giorgia; Di Vincenzo, Matteo; Scorza, Maristella; Franceschini, Christian; De Ronchi, Diana; Fiorillo, Andrea; Plazzi, Giuseppe (Frontiers in Psychology, 2025)
Adolescent suicide remains a critical global public health challenge, with rising incidence rates necessitating urgent action. This narrative review presents a comprehensive strategy for reducing suicide risk among adolescents by synthesizing current evidence on risk factors, early detection, intervention, and prevention. Key risk factors include mental health disorders, substance use, trauma, and social determinants such as bullying and family dynamics. Schools, healthcare systems, and community-based initiatives play a vital role in early detection and intervention. This review examines evidence-based strategies, including universal screening, expanded access to mental health care, and targeted interventions such as cognitive behavioral therapy (CBT) and dialectical behavioral therapy (DBT). It also explores the impact of public health campaigns, policy reforms, and technology-driven approaches on strengthening adolescent mental health awareness and resilience. A multi-sectoral, culturally sensitive approach—one that prioritizes the voices of adolescents, engages families and promotes health equity—is essential for reducing the risk of suicide and enhancing youth well-being globally. This review underscores the urgent need for enhanced suicide prevention policies, improved mental health service accessibility, and the integration of digital tools in adolescent care. Addressing research gaps through longitudinal studies and real-world implementation trials will be key in shaping future strategies to reduce adolescent suicide rates globally.